RANCANG BANGUN PENGENDALIAN TEGANGAN MENGGUNAKAN KONTROL PID-ARDUINO PADA PROTOTIPE MINI PLANT MIKROHIDRO - Dedi Nugroho; Dirga Wahyu Prasetyo; Bustanul Arifin (TESLA: Jurnal Teknik Elektro, 2022)
Microhydro power plant is an alternative for producing small-scale electrical energy uses hydropower. Microhydro has three main components, water, turbine and generator. In the environment , it can also be used as a microhydro power plant on a home scale. The components needed to make microhydro prototype are water reservoirs, valves, MOV,generators, flowmeters, voltage sensors,LED . The water reservoir is installed as high as 4 meters. MOV is used as an actuator to control the flow of water to adjust the degree of valve opening automatically. Generator is connected to convert mechanical energy into electrical energy, flowmeter to determine the debit value and a voltage sensor is connected. The system will be connected to the load of an LED light. When the lamp load changes, it is expected that the voltage generated by the generator remains stable. To regulate the voltage to remain stable, voltage control is carried out by adjusting the degree of valve opening using a PID control system. Voltage control with PID control based on Ziegler Nichols theory with oscillation method. Through experimentation, it was obtained that the KP = 0.9, Ki = 0.45 and Kd = 0.45 constants were the most optimal because the response of the oscillating system was 1.15 seconds shorter. The time required for the voltage to stabilize to the setpoint from the start of the system being turned on is 46.20 seconds. The greater the degree of valve opening, the greater the voltage generated, because the debit produced is greater.